Pattern of family planning practices among Janani Suraksha Yojana beneficiaries: Central Uttar Pradesh, India - Kashyap, Saurabh; Kumari, Reema; Masood, Jamaal; Verma, Sheetal; Jain, Savita; Kumar, Anil (International Journal Of Community Medicine And Public Health, 2017)
Background: Short birth interval adversely affects the maternal and neonatal health. The use of contraceptive methods is still one of the biggest challenges in developing countries despite various programs. Janani Suraksha Yojana was started with aims to achieve national targets for contraception. Methods:The present study was a cross sectional study conducted in Lucknow district amongst the women admitted in three blocks of rural area health centers. The blocks were selected by simple random sampling method. A total of 400 women who delivered in the labor wards of the health centers were interviewed and enrolled. Results: In the present study, out of 400 mothers, 39(9.8%) mothers had their first delivery below the age of 18 yrs. According to modified Udai Pareek Scale, 56.3% of the mothers belonged to 5th socio-economic status. Birth spacing was the purpose to use family planning (FP) methods among 121(55.5%) of the mothers. The use of FP method was significantly associated with occupation of mothers and their husband and education of mothers. It was also found that the use of FP method was significantly (p=0.001) higher among those beneficiaries who had birth interval > 3 years (72.1%) in contrast to 2-3yrs (68.8%), 1-2yrs (60.2%) and < 1yr (36.4%). Conclusions:JSY is a promising program for promotion of contraception. Knowledge about the family planning methods should be provided to the beneficiaries during their ANC visits as during this period they are more receptive to family planning methods.